Anaesthetic management of spinal muscular atrophy in a patient with pneumothorax: a case report - Rasheed, Madeeha; Ahsan, Khalid (Journal of the Pakistan Medical Association, 2025)
One of the most prevalent hereditary neuromuscular disorders is spinal muscular atrophy (SMA). Progressive muscular weakness and an irreversible loss of alpha motor neurons in the spinal cord are the hallmarks of SMA and are associated with increased sensitivity to opioids and muscle relaxants. SMA is classified clinically into four categories according to its severity and age of onset, which poses a challenge for the anaesthesiologist. Although general anaesthesia can be given, it is preferable to avoid muscle relaxation. We are reporting the anaesthetic management of a patient with type 3 SMA, diagnosed with a case of bullous lung disease. The procedure planned was thoracoscopy and pleurodesis/pleurectomy under general anaesthesia at the Aga Khan University Hospital, Karachi, in August 2022. This case report highlights the importance of individualised care in SMA patients, emphasising the need for careful planning and consideration of patient-specific factors. Keywords: Spinal Muscular Atrophy, Anaesthesia, Thoracoscopy, Pleurodesis.